Clinical Outcomes of Early Versus Delayed Appendectomy - Bhattarai, Amit; Adhikari, Dinesh; Kafle, Aakash; Adhikari, Bigyan; Mahato, Aakash; Shreewastav, Kritika (Journal of Nobel Medical College, 2026)
Background: Acute appendicitis is one of the most common surgical emergencies worldwide. The controversy still exists about the timing of operation for appendicitis. The aim of this study was to compare the outcomes between early appendectomy and delayed appendectomy and assess the feasibility of delayed operation. Materials and Methods: A hospital based prospective comparative study of patients diagnosed with acute appendicitis was conducted at Nobel Medical College Teaching Hospital from April 2025 to July 2025. Ethical clearance was taken from the Institutional Review Committee. Parameters such as, operative time, postoperative complications, duration of hospitalization, and time to return to normal activity were evaluated. Results: Out of one hundred twenty-one patients who underwent laparoscopic appendectomy, mean age of the patients in Group A was 33.16 +/- 10.38 years and that in Group B it was 35.23 +/- 9.16 years. Male: Female ratio was 7:8 in Group A and 2:3 in Group B. The Early group had an average surgery time of 56.67+/-11.88 minutes and an average hospital stay of 2.33+/-0.60 days whereas the Delayed group showed a slightly higher mean surgery time of 57.50+/-11.18 minutes and a longer average hospital stay of 2.70+/-0.70 days. During follow up in OPD, surgical site infection was noted in eight patients of Group A and five patients of Group B. Overall, only hospital stay showed a meaningful difference between the groups, while other variables remained comparable. Conclusion: Early and delayed laparoscopic appendectomy yield similar clinical outcomes in patients with acute appendicitis. While delayed appendectomy appears to be a safe and feasible alternative, early appendectomy is associated with a significantly shorter hospital stay and may provide economic benefits through reduced hospitalization and earlier recovery.